Bernhard Varenius (1622-1650) - Schuchard, Margret (Brill's studies in intellectual history, 2007)
Prefatory Note / Vorbemerkung; Chronological Table -- The Life of Bernhard Varenius; Bernhard Varenius -- Family Background; Bernhard Varenius -- Stemma of Editions; List of Illustrations; Introduction; I VARENIUS' FORMATIVE YEARS IN THE CONTEXT OF HIS TIME / VARENIUS IM BILDUNGSHORIZONT SEINER ZEIT; II VARENIUS AS A TRANSMITTING AGENT OF KNOWLEDGE -- JAPAN / VARENIUS ALS WISSENSVERMITTLER EINER FREMDEN WELT -- JAPAN; III GEOGRAPHIA GENERALIS AND ITS LEGACY / DIE GEOGRAPHIA GENERALIS UND IHRE NACHWIRKUNGEN; Appendix: Extracts from Geographia Generalis (1650) Translation by Ernst-Christian Volkmann